Educational training intervention on workplace violence among healthcare workers - Ibrahim, Mohd Safwan; Ariffin, Ahmad Azuhairi (Community Health Society Malaysia, 2019)
Background: Workplace violence is defined as incidents where staff are abused, threatened or assaulted in circumstances related to their work, including commuting to and from work, involving an explicit or implicit challenge to their safety, well-being or health. In healthcare setting, it can bring serious consequences to the workers, organization and quality of patient care. Educational training is one of the methods to reduce the incident and prepare the workers in order to face this challenge. This manuscript aims to analytically analyse educational intervention on workplace violence among health workers. Materials and Methods: Systematic review was conducted via Pubmed and ScienceDirect, using keywords of (aggression OR violence) AND healthcare workers) AND (education OR training). A total of 1914 articles from search engines and other sources were obtained. After screening, 12 articles were included in this manuscript. Result: There are 12 studies in this review including two randomised controlled trials (RCTs), five quasi-experimental design and five before-after experimental design. Studies were conducted across various healthcare organizations and most of these were hospitals. Most of the studies include multiple modules including de-escalating techniques, assessing risk of violence, communication skills, workers responsibility, notification and post incident procedure, and legal aspect of workplace violence. Studies showed improvement in knowledges, attitude, confidence and coping. Conclusion: Majority of this evidence were weak and more high-quality research is needed in this area of study. Sound methodology and controlled study design to avoid biases should be done to prove the effectiveness of educational learning in workplace violence.